2012
DOI: 10.1134/s1069351312020012
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface geophysics: Complex investigations of the lithosphere-atmosphere interactions

Abstract: The key trends and problems in the study of interactions between the geospheres in the near sur face areas of the continental crust of the Earth which are of most interest for the formation of living environ ment are formulated. The main periodicities in the variations of geophysical fields determining the natural environmental rhythms are determined. The interactions and transformations of geophysical fields (electric field in the ground and in the atmosphere, radon emanation field, and the field of microseis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Адуш кин и А.А. Спивак [Adushkin, Spivak, 2012] показали широкое распространение микросейсм с частотами 10 -4 -10 -5 и меньше на земном шаре. Их в основном образуют около 1 млн землетрясений с М≥2 и более 10000 -с М≥4.…”
Section: деформационные волны регионального и трансрегионального распunclassified
“…Адуш кин и А.А. Спивак [Adushkin, Spivak, 2012] показали широкое распространение микросейсм с частотами 10 -4 -10 -5 и меньше на земном шаре. Их в основном образуют около 1 млн землетрясений с М≥2 и более 10000 -с М≥4.…”
Section: деформационные волны регионального и трансрегионального распunclassified
“…Currently, both in Russia and abroad, seismic exploration is a dominant geophysical method, which refers to indirect exploration methods (Adushkin & Spivak, 2012). Despite new modifications, including three-dimensional modeling, the "success rate" among a number of attempts to drill exploratory wells, according to seismic prospecting, still does not exceed 0.5, i.e.…”
Section: Research Questionsmentioning
confidence: 99%
“…In seismically active regions, where the continuous seismotectonic process is accompanied by more intensive deformations of rock, anomalous disturbances of different geophysical fields are observed during earthquake preparation and might be considered as precursors (Adushkin and Spivak, 2012). Studies in Kamchatka (Larionov et al, 2014;Rulenko et al, 2014;Marapulets et al, 2011) showed that pre-seismic anomalous fluctuations in acoustic, atmospheric-electric and emanation fields occur as the result of relative microdisplacements of nearsurface sedimentary rock fragments.…”
Section: Introductionmentioning
confidence: 99%